Determinan Rumah Tangga Tidak Cukup Pangan Periode 2015 – 2022 - Arrohmah, Laila; Putri, Afidita Nabila; Setya P, I Gede Nyoman; Lestari, Zahra Ayu; Manik, Rizky Wahyuda; Budiasih, Budiasih (Politeknik Statistika STIS, 2023)
Sustainable Development Goals (SDGs) to zero hunger in Indonesia can be seen from several indicators. One indicator that can assess the success of SDGs for zero hunger is the percentage of households with insufficient food status. Almost all provinces have not been able to achieve the target of the minimum proportion of households with insufficient food status each year. This study aims to identify the factors that influence the percentage of households with insufficient food status. The data used is panel data with observations from 34 provinces in Indonesia for the 2015 - 2022 period. This research uses panel data regression analysis method with the best model is Fixed Effect Model (FEM). The results of this study show that food inflation average, growth in per capita, production of dry milled unhusked rice, and the percentage of poor people affect the percentage of households with insufficient food status in Indonesia in 2015 - 2022.